Experimental study on masonry infill walls under blast loading - Pereira, João Miguel (2014)
The vulnerability of the masonry envelop under blast loading is considered critical due to the risk of loss of lives. The dynamic behaviour of masonry infill walls subjected to dynamic out-of-plane loading was experimentally investigated in this work. Confined underwater blast wave generators (WBWG) allows applying an extremely high rate conversion of the explosive detonation energy into the kinetic energy of a thick water confinement, which, in turn, allows a surface area distribution avoiding the generation of high velocity fragments and reducing atmospheric sound wave. In the present study water plastic containers, having in its centre a detonator inside a cylindrical explosive charge, were used. Tests were performed in unreinforced walls with 1.7 by 3.5 m, which are 1:1.5 scaled. Besides the usage of pressure and displacement transducers, pictures were recorded with high-speed video cameras to process the deflections and identify failure modes.